Effect of Fuel on Phase Formation of Nanocrystalline Bismuth Ferrite (BiFeO3). (2015) - Silambarasan, P.; Vairavel, M.; Kumar, G. Ramesh; Raj, S. Gokul
Abstract: Single phase bismuth ferrite (BFO) was synthesized by sol gel auto combustion method using various fuels such as Citric acid, Urea, DL Malic acid, L(+) Tartaric acid, EDTA and Ethylene glycol. Phase formation was confirmed using XRD analysis and effect of fuels on phase formation is discussed in detail. Simultaneous Thermo gravimetric-differential thermal analysis (TG-DTA) was carried out to investigate its phase evolution. Phase formation on the single step of nanocrystalline form of bismuth ferrite was obtained for the first time. The results were discussed in detail.